2014
DOI: 10.1111/jcmm.12250
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects rat cerebellar granule cells against electromagnetic field‐induced increases in Na+ currents through intracellular Ca2+ release

Abstract: Although melatonin (MT) has been reported to protect cells against oxidative damage induced by electromagnetic radiation, few reports have addressed whether there are other protective mechanisms. Here, we investigated the effects of MT on extremely low-frequency electromagnetic field (ELF-EMF)-induced Nav activity in rat cerebellar granule cells (GCs). Exposing cerebellar GCs to ELF-EMF for 60 min. significantly increased the Nav current (INa) densities by 62.5%. MT (5 μM) inhibited the ELF-EMF-induced INa inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This agonist is known to have 90-folds more selectivity toward MT2 receptor (pKi =10.30) subtype over MT1 (pKi =8.34) with a 6-fold higher affinity toward MT2 receptor subtype than MLT 16. IIK-7 is known to promote sleep and protect the cells from electromagnetic stress like MLT 17,18. However, to date, there are no reports on the anti-nociceptive properties of this agonist.…”
Section: Introductionmentioning
confidence: 99%
“…This agonist is known to have 90-folds more selectivity toward MT2 receptor (pKi =10.30) subtype over MT1 (pKi =8.34) with a 6-fold higher affinity toward MT2 receptor subtype than MLT 16. IIK-7 is known to promote sleep and protect the cells from electromagnetic stress like MLT 17,18. However, to date, there are no reports on the anti-nociceptive properties of this agonist.…”
Section: Introductionmentioning
confidence: 99%
“…Whether GDF-15 modulates [Ca 2+ ] i in CGNs and the mechanisms that are involved is unknown. In the present study, we evaluated the effect of GDF-15 on [Ca 2+ ] i using Ca 2+ imaging while simultaneously recording inward Ca 2+ current ( I Ca ), since changes in [Ca 2+ ] i in CGNs are associated with Ca 2+ influx-dependent Ca 2+ release [ 20 , 21 ]. We also examined whether the same signalling pathways and receptors identified in our previous study are activated by GDF-15 under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study examined the impact of magnetic field exposure on oxidative stress created by EMFs and identified protective impacts 27. In our study, we found that treatment with an antioxidant (MLT or GL) caused the TE concentrations (that were changed by high-voltage ELF-EMFs) to return to their normal values.…”
Section: Discussionmentioning
confidence: 57%